2006
DOI: 10.1002/mame.200600191
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Mechanical Behavior of Carbon‐Nanotube‐Filled Latex

Abstract: Summary: Composite films were prepared from a mixture of poly(vinyl acetate) latex and SWNTs. SEM images reveal a segregated SWNT network that grows heavier with increasing concentration. Nanotube segregation is the result of excluded volume created by the much larger polymer particles in the latex. Thermal conductivity exhibits a sharp rise with increasing quantity of nanotubes, although the maximum value is only 10% greater than that of the polymer matrix due to large thermal interface resistance. Storage mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(53 citation statements)
references
References 74 publications
2
51
0
Order By: Relevance
“…The percolation threshold of CPCs have been shown both experimentally and theoretically to decrease with filler aspect ratio 2, 3. CNTs have been extensively investigated as fillers for polymer nanocomposites,4–14 and their high aspect ratio and excellent conductivity makes them one of the best conductive nanofiller candidates for CPCs. It has been shown that CPCs based on CNTs can reach percolation thresholds as low as 0.0025 wt.‐% in low viscosity systems such as epoxy resins 11, 15, 16.…”
Section: Introductionmentioning
confidence: 99%
“…The percolation threshold of CPCs have been shown both experimentally and theoretically to decrease with filler aspect ratio 2, 3. CNTs have been extensively investigated as fillers for polymer nanocomposites,4–14 and their high aspect ratio and excellent conductivity makes them one of the best conductive nanofiller candidates for CPCs. It has been shown that CPCs based on CNTs can reach percolation thresholds as low as 0.0025 wt.‐% in low viscosity systems such as epoxy resins 11, 15, 16.…”
Section: Introductionmentioning
confidence: 99%
“…When combined with nanosized fillers, the polymer particles and the filler may create a peculiar segregated network. The corresponding material, after drying and 'hot compaction', may show excellent properties at very low filler concentration [3][4][5][6] compared to a melt blended version containing the same polymer and filler. The advantage of this latex compounding process is that the expensive chemical modification of the fillers can be avoided if the filler is itself water swellable or dispersible [7].…”
Section: Introductionmentioning
confidence: 99%
“…This phenomenon is likely a result of the larger bundles of SWNT having a greater resistance to bending, effectively increasing the stiffness over long distances. It should also be noted that these nanotubes are more strongly networked in their bundled state,18 which is known to enhance composite modulus 23…”
Section: Resultsmentioning
confidence: 99%